3-Hydroxybenzo[a]pyrene in the urine of workers with occupational exposure to polycyclic aromatic hydrocarbons in different industries. Issue 4 (20th April 2007) - Förster, K; Preuss, R; Roßbach, B; Brüning, T; Angerer, J; Simon, P
Abstract : Objectives: This study was conducted to assess external and internal exposure of workers to polycyclic aromatic hydrocarbons (PAHs). In this context, the analytical and diagnostical reliability of 3-hydroxybenzo[a]pyrene (3OH-BaP) as a biomarker of internal exposure to PAHs was established. Methods: Ambient and biological monitoring was carried out of 225 PAH-exposed employees of different industries. External exposure was determined by personal air sampling and analysis of 16 EPA-PAH. Internal exposure was examined by the urinary metabolites 3OH-BaP, 1-hydroxypyrene (OH-Pyr) and monohydroxylated phenanthrenes (OH-Phens). Results: Benzo[a]pyrene (BaP) was detected at all workplaces. Concentrations in the breathing zone of the workers ranged from below the limit of detection up to 44.3 μg/m 3 . In biological monitoring, urinary 3OH-BaP was found in median concentrations of 0.8 ng/g creatinine (crea) and the 95th percentile of 6.7 ng/g crea. The results ranged from the limit of detection up to 19.5 ng/g crea. Only 1% of the analysed samples showed concentrations below the limit of detection (0.05 ng/l). Regarding median concentrations, workers in coking plants showed lower 3OH-BaP concentrations (0.5 ng/g crea) than those employed in the production of fireproof material in refractories (1.1 ng/g crea), converter infeed (1.2 ng/g crea) and graphite electrode production (1.3 ng/g crea). Strong correlations of 3OH-BaP with OH-Pyr and the sum of OH-Phens were found for the workplaces converter infeed, coking plants and graphite electrode production (rPearson ranging from 0.618 to 0.867, p<0.001). The poor correlation of BaP in the air and 3OH-BaP in urine is most probably caused by routes of uptake other than via air—for example, dermal uptake. Conclusion: 3OH-BaP as a metabolite of the carcinogenic BaP could be shown to be a diagnostically specific and sensitive biomarker for determining the internal exposure of workers in different industries. Using this method, the estimation of health risks for workers can be fundamentally improved, because the 3OH-BaP represents the group of carcinogenic PAHs. The procedure for analysing 3OH-BaP is complex, but it is robust and produces reliable results.